2009
DOI: 10.1149/1.3212894
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Composite Electrode with High Capacity and Long Cycle Life

Abstract: International audienceA nanosilicon-based composite electrode that can achieve more than 700 cycles at a high capacity of 960 mAh/g of electrode was prepared using aqueous processing in an acidic medium. The buffering of the aqueous solution is mandatory to promote covalent bonding between Si particles and the carboxymethyl cellulose (CMC) binder. The latter is claimed to allow the formation of mechanically stronger contacts within the composite electrode in addition to the CMC bridging of the Si and carbon bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
263
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(274 citation statements)
references
References 20 publications
7
263
2
2
Order By: Relevance
“…For example, phytic acid, a naturally occurring molecule consisting of six phosphoric acid groups, can be used as both the gelator and dopant to react with the aniline monomer by protonating the nitrogen groups on polyaniline (PANi), leading to the formation of a 3D interconnected network structure 38 . In this work, when SiNPs are mixed into the solution during polymerization, the phosphoric acid groups in the phytic acid molecules can potentially bind with the SiO 2 on the Si particle surfaces via hydrogen bonding, which was thought to contribute to the improved cycle lifetime for PAA, CMC and alginate binders with carboxylic acid groups [32][33][34]36 . This interaction can also result in the conformal coating of phytic acid molecules on the surface, which may further crosslink with aniline monomers during polymerization to generate a conformal conductive coating.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, phytic acid, a naturally occurring molecule consisting of six phosphoric acid groups, can be used as both the gelator and dopant to react with the aniline monomer by protonating the nitrogen groups on polyaniline (PANi), leading to the formation of a 3D interconnected network structure 38 . In this work, when SiNPs are mixed into the solution during polymerization, the phosphoric acid groups in the phytic acid molecules can potentially bind with the SiO 2 on the Si particle surfaces via hydrogen bonding, which was thought to contribute to the improved cycle lifetime for PAA, CMC and alginate binders with carboxylic acid groups [32][33][34]36 . This interaction can also result in the conformal coating of phytic acid molecules on the surface, which may further crosslink with aniline monomers during polymerization to generate a conformal conductive coating.…”
Section: Resultsmentioning
confidence: 99%
“…Various polymer binders other than traditional polyvinylidene difluoride (PVDF), including polyacrylic acid (PAA), carboxy-methyl cellulose (CMC), poly(9,9-dioctylfluorene-co-Suorenone-comethylbenzoic acid) (PFFOMB) and alginate, have been found to enhance the cycle life 14,15,[32][33][34][35][36] . The cycle life improvement when using PAA, CMC and alginate binders was attributed to the high polymer modulus values and the binding between the functional groups on the polymers with the surface oxide on the Si particles.…”
mentioning
confidence: 99%
“…From these mechanisms, it is likely that at high pH values, the dominant interaction is the hydrogen bonding interaction between the CMC and the Si nanoparticle. Interestingly, Guyomard et al reported that an esterification reaction between Si-OH on the Si surface and the COOH of the CMC binder preferentially occurred at pH = 3 and that this covalent bonding could remarkably improve the cycling performance of nano-Si anodes [32]. Oh et al investigated a polyvinyl alcohol (PVA) linear-type polymer with many hydroxyl groups, showing that it can form hydrogen bonds with active materials and the current collector as a binder for Si/graphite composite anodes [33].…”
Section: Homopolymersmentioning
confidence: 99%
“…At these low voltages, the amorphous Li-silicides (a-Li x Si) formed on lithiation are converted to crystalline phases such as crystalline Li 3.75 Si (c-Li 3.75 Si) 5,12,[22][23][24][25][26][27] , a process that is associated with a large overpotential on delithiation. This approach differs from other practical strategies to improve capacity retention that limit the Si cycling regimes to B1,200-1,500 mAh g À 1 , cycling at higher potentials between different a-Li x Si compositions 3,28 . To utilize Si to its full potential using these very different cycling regimes, an understanding needs to be developed of the different structural processes that occur, the kinetics of the various transformations and how they correlate with capacity retention.…”
mentioning
confidence: 98%